Minimal change nephrotic syndrome and Graves’ disease in a Nigerian child (2008)
We report a 12 year old Nigerian boy with steroid sensitive nephrotic syndrome who developed Graves’ disease 12 months after the diagnosis of nephrotic syndrome. He had two relapses of the nephrotic syndrome with early response to steroids on both occasions. Renal biopsy showed normal findings on light microscopy. Graves’ disease is rare among black African children, minimal change nephrotic syndrome is also not commonly reported among them. The coexistence of these two disorders in our patient underscores possible similar immunologic mechanisms in the aetiology of both diseases.